Decomposição de grupos e invariantes ends - Ricieri, Marina Marcia [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
Um grupo G se decompõe sobre um subgrupo S se G þe um produto livre com subgrupo amalgamado S ou uma extensão HNN. Neste trabalho, propusemo-nos a relacionar, sob alguns aspectos, decomposição de grupos e invariantes ends. Mais precisamente, demonstramos os teoremas da forma normal para produtos livres com subgrupo amalgamado e extensões HNN e apresentamos alguns resultados relativos `a teoria de grafos, ends de grupos e pares de grupos, finalizando com a prova de um teorema de Kropholler e Roller, sobre decomposição de grupos, envolvendo a obstrução sing.

A group G splits over a subgroup S if G is a free product with amalgamated subgroup S or an HNN extension. In this work, we are concerned in relating, under some aspects, splittings of groups and invariants ends. More precisely, we prove the theorems normal forms for free products with amalgamated subgroup and HNN extensions and we present some results related with the theory of graphs, ends of groups and pairs of groups, concluding with the proof of a theorem by Kropholler and Roller, on decomposition of groups, involving the obstruction sing.
Keywords: Topologia algebrica; Invariantes; Decomposição de grupos; Invariantes ends; Obstrução sing; Free products with amalgamated subgroup; HNN extension; Splittings of groups